Applying a Multiple Convergent Process in Achieving a Successful of New Product Developmen - Masyhuri, Muhammad (ADPEBI International Journal of Business and Social Science, 2022)
New Product Development (NPD) is critical for companies to improve their business results. However, few companies can benefit from such a process because it is difficult to determine how and which NPD processes should be designed to develop a leading-edge product. The objective of this study is to find out the appropriate and best approach for implementing an NPD process in a company. The Multiple Convergent Process (MCP) framework model is applied by borrowing the framework model of (Baker & Hart, 2007). The objective of the MCP framework model is to apply a parallel mechanism of NPD phases to work towards the same point or common outcome without delaying the next phase. This study applies a descriptive research method by describing the steps of the MCP model and using literature reviews. Fifty-two publications from 1990 to 2018 were reviewed. Major and related topics such as NPD, innovation, multiple convergent points, idea generation - evaluation - concept and selection, and factors for successful NPD were considered.